PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA MALUKU - Alfonso, Pocerattu V. (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
Ministry of law and human rights In the the territory of Maluku was one of many agiencies whose employment performance was influenced by education and training. This makes education and training invaluable to employees in order to perform a job well so that purpose of the offices could be reached. So the study aims to see how much educations and training affect office works performance.This study is an empirical study, with the population being all employees of law and human right in the the ministry of Maluku. The sampling technique used an approach using the Slovin formula and the sample size was 57 respondents. The analysis technique used is simple linear regression analysis, where the hypothesis test uses t-statistical test to test the partial regression coefficient with a significance level of 0.05 or 5%.A study of 57 respondents concluded that competence as a positive influence to the performance of employees of Ministry Of Law And Human Right In The Province of Maluku. It is proven by the coefficient determin obtained from this study of 0,761 it show that 76,1% employees performance in the affected by education and training while 23,9% is affected by other variables. Based on these results it is concluded that Competence Affect The Performance Of Employees Of Region’s Of Law And Human Rights The Ministry Of Maluku.